Total Contact Cast after Sole Free Flap Reconstruction for Early Ambulation - Yamashita, Yutaro; Abe, Yoshiro; Bando, Mayu; Mima, Shunsuke; Yamasaki, Hiroyuki; Nagasaka, Shinji; Mineda, Kazuhide; Hashimoto, Ichiro (Archives of Plastic Surgery, 2025)
Background Free flap reconstruction can be performed in patients with chronic limb-threatening ischemia (CLTI). However, early walking training may increase the risk of wound dehiscence and prolong hospitalization. Total contact cast (TCC) treatment effectively addresses diabetic plantar ulcers by immobilizing the foot and distributing weight away from the ulcer area. This study aimed to assess the effect of postoperative TCC use on early limb loading and hospital stay in patients with CLTI with free flaps.Methods Patients with CLTI who underwent free flap reconstruction between 2006 and 2023 were enrolled in this study. Postoperative time until weight-bearing initiation was compared between the TCC (n = 5) and non-TCC groups (n = 7).Results The time to the initiation of weight-bearing on the affected limb was 52.3 ± 33.2 days in the non-TCC group and 19.8 ± 3.56 days in the TCC group (p = 0.105). The wound dissection rates were 42.9% (3/7) in the non-TCC group and 20% (1/5) in the TCC group (p = 0.408). At discharge, 28.6% (2/7) of the non-TCC group and 20% (1/5) of the TCC group had ulcers (p = 0.735). The average flap size was 149 ± 69.1 cm2 in the non-TCC group and 95.6 ± 73.1 cm2 in the TCC group (p = 0.268).Conclusion Postoperative TCC use after free flap foot reconstruction may lead to early weight-bearing of the affected limb. Further studies with larger numbers of cases are needed.
Keywords: chronic limb-threatening ischemia; total contact cast; free flap; diabetic foot ulcer